Structure of Professional Competence of Future Software Engineers - Kruglyk, Vladyslav; Osadchyi, Viacheslav (Pedagogical Discourse, 2016)
The paper analyses concepts of engineer, programmer and software engineer. The special attention is given to the idea of the integrative character of professional activity of software engineer who works not only with a computer as a technical device, but with information. Because of the fact that the main professional activity of a software engineers is programming or software engineering in the process of which they develop a plan and action order, check the accuracy and quality of results, it is necessary to define a concept of software engineer. The authors introduce their own definition of this concept from the position of methods applied for software development. The paper presents thoughts of scientists and IT-specialists concerning professional qualities of software engineers. Scholars consider mathematical skills, an engineering habit of mind, analytical thinking, fundamental knowledge of computer science and programming to be important qualities. The authors find that future software engineers have to develop labile and divergent thinking. On the basis of the analysis of professionally important qualities of software engineers the list of competences of future software engineers is produced and summarized, which includes seven components of professional competence of software engineers, namely programming competence, digital competence, mathematical competence, engineering competence, personal and professional competence, management competence and communicative competence. Stages of professional competence development of future software engineers in higher educational establishments are given (integrative stage, basic stage, main stage, qualification stage and professional stage). The essence of components of professional components of future software engineers is determined. Key words: professional training, software engineer, professional competence.